Incidence of congenital gallbladder anomalies and clinical significance - Batmaz, Ibrahim; Gul, Yeliz; Sanli, Cengiz; Bulu, Gulay; Senocak, Ahmet; Kavak, Salih Burcin (Bayrakol Medical Publisher, 2021)
Aim: In this study, we aimed to investigate the prevalence of congenital gall bladder anomalies and their importance in perinatal follow-up. Material and Methods: This study was conducted by retrospectively examining the data of 3080 patients who applied to Firat University Gynecology and Obstetrics Outpatient Clinic between 14-37 weeks of gestation between December 2018 and November 2020. Obstetric characteristics of the patients such as age, pregnancy number, abortion, parity and body mass index were recorded. In all cases, the fetal gallbladder was examined in the axial plane, used to measure the abdominal circumference. Routine evaluation was performed in the axial plane of the abdomen, where other structures such as the stomach and umbilical vein were visible in this plane. After monitoring the gall bladder, the echogenicity of its contents, the shape of the sac and its position in the abdomen were evaluated. The ultrasonographic features of the cases with gallbladder abnormalities detected were recorded. Results: Between the dates of the study, 2120 pregnant women were included in the study. Gallbladder abnormality was detected in five cases. Accordingly, the incidence of gallbladder abnormalities was found to be 0.23%. The incidence of gall bladder abnormalities in the study population was found to be 1/370. Gallbladder abnormality was isolated in all cases, and no chromosomal abnormality was found. No additional anomalies were found in newborn babies in the postpartum controls of the cases. Discussion: Gallbladder evaluation is part of extended fetal screening. Gallbladder anomalies appear as relatively rare and mostly benign anatomical variations. By informing the family, it is ensured that appropriate follow-up in postnatal life is obtained.
Keywords: Gall Bladder; Anomalies; Ultrasonography; Incidence